FIP Position Paper on Qualification of Paddle and Basket Dissolution Apparatus - Brown, Cynthia K. (Springer US, 2009)
The qualification process for ensuring that a paddle or basket apparatus is suitable for its intended use is a highly debated and controversial topic. Different instrument qualification and suitability methods have been proposed by the pharmacopeias and regulatory bodies. In an effort to internationally harmonize dissolution apparatus suitability requirements, the International Pharmaceutical Federation's (FIP) Dissolution/Drug Release Special Interest Group (SIG) reviewed current instrument suitability requirements listed in the US, European, and Japanese pharmacopeias and the International Conference on Harmonization (ICH) Topic Q4B on harmonization of pharmacopoeial methods, in its Annex 7, Dissolution Test General. In addition, the SIG reviewed the Food and Drug Administration (FDA) Draft Guidance for Industry, “The Use of Mechanical Calibration of Dissolution Apparatus 1 and 2—Current Good Manufacturing Practice (CGMP)” and the related ASTM Standard E2503-07. Based on this review and several in-depth discussions, the FIP Dissolution/Drug Release SIG recommends that the qualification of a dissolution test instrument should be performed following the calibration requirements as indicated in the FDA (draft) guidance. If additional system performance information is desired, a performance verification test using US Pharmacopeia Reference Standard tablet or an established in-house reference product can be conducted. Any strict requirement on the use of a specific performance verification test tablet is not recommended at this time.